The role of the clinical nurse specialist in caring for patients with prostate cancer: a narrative review - Lopes MH (Dove Medical Press, 2014)
Maria Helena Baena de Moraes Lopes,1 Rosângela Higa21Faculty of Nursing, University of Campinas, Campinas, São Paulo, Brazil; 2Nursing Department, Prof Dr José Aristodemo Pinotti Women’s Hospital, CAISM, University of Campinas, Campinas, São Paulo, Brazil Abstract: Prostate cancer, the leading cancer among men, constitutes a serious public health problem worldwide. Its treatment and care require a multi-professional approach. This descriptive review was conducted to establish the role of the clinical nurse specialist in providing prostate cancer care. The CINAHL, MEDLINE, PubMed, Medscape, LILACS, BDENF, and Cochrane databases were searched to identify relevant publications up to September 2013 written in Portuguese, English, and Spanish, using the Electronic Information Access Program and Coordination for the Improvement of Higher Education Personnel (CAPES) Periodicals Portal in the search system of the Digital Library of the University of Campinas, São Paulo, Brazil. Articles not present in these databases or that did not discuss nursing care for men with prostate cancer and/or their families were excluded. Analysis of 20 studies selected according to these criteria revealed four important aspects of specialized nursing care: care provided 1) at the time of prostate cancer diagnosis; in the 2) pretreatment and 3) posttreatment periods; and 4) in the assistance of partners and family members of men with prostate cancer. The studies included in the analysis showed that physical and psychological problems, such as loss of energy and motivation, functional impairment, and loss of sex life, were relevant to nursing care. They confirmed that nursing care actions for men with prostate cancer should start at the time of diagnosis, when patients must participate in deciding the best course of treatment. During the prostatectomy period, care involves preoperative preparation, which is fundamental for recovery and adaption to postoperative sequelae. Family members, especially partners, should also receive attention and support during this period. The results allowed the conclusion that the role of the clinical nurse specialist in the care of men with prostate cancer is broad and essential, but interventions and new strategies of care need to be evaluated through well-designed clinical studies. Keywords: prostatic neoplasm, nursing care, nurse clinician, prostatectomy, review literature as topic